2005
DOI: 10.2106/jbjs.d.01870
|View full text |Cite
|
Sign up to set email alerts
|

Management of Cubitus Varus and Valgus

Abstract: Step-cut translation osteotomy, with a wedge-shaped osteotomized surface, fixed with a Y-shaped humeral plate is a relatively simple procedure resulting in very firm fixation that allows early movement of the joint with good clinical results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
78
0
13

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 7 publications
0
78
0
13
Order By: Relevance
“…Several investigators reported assessment of varus and extension deformities using conventional radiography and other clinical measurements. 9,13,20,28,30,32 Rotational deformities of the humerus have been studied with reference to the difference in the rotational range of shoulder motion, compared with the contralateral shoulder, 39 as well as by 2-dimensional (2D) approaches using proximal and distal cross-sectional computed tomography (CT) slices of the humerus. 11,37 However, all these studies evaluated only 1 or 2 components of the deformity.…”
mentioning
confidence: 99%
“…Several investigators reported assessment of varus and extension deformities using conventional radiography and other clinical measurements. 9,13,20,28,30,32 Rotational deformities of the humerus have been studied with reference to the difference in the rotational range of shoulder motion, compared with the contralateral shoulder, 39 as well as by 2-dimensional (2D) approaches using proximal and distal cross-sectional computed tomography (CT) slices of the humerus. 11,37 However, all these studies evaluated only 1 or 2 components of the deformity.…”
mentioning
confidence: 99%
“…Neben der Plattenosteosynthese werden die Fixation mit Kirschner-Drähten, Klammern, Schrauben, Drahtschlingen und äußerem Spanner sowie verschiedenste Osteotomien, wie die French-Osteotomie, Domosteotomie, "step cut"-Osteotomie und andere, beschrieben [3,8,11,14,15,20]. Zugänge von medial und lateral mit additivem und subtraktivem Vorgehen (autogener Keil aus dem Beckenkamm oder Entfernung eines lateral offenen Keils) werden verwendet.…”
Section: Resultsunclassified
“…Ein Cubitus varus (Abbildung 1a) stellt die häufigste Komplikation nach suprakondylären Frakturen des Humerus dar; die Inzidenz wird mit 3-57% angegeben [3,5,10,14,17]. Ein Cubitus valgus (Abbildung 1b) nach suprakondylären Frakturen wird dagegen selten beschrieben [2,5,14].…”
Section: Vorbemerkungenunclassified
See 1 more Smart Citation
“…This should avoid secondary joint and bone reshaping which would make correction more difficult or even impossible. [10]. Aus dem gleichen Grund und wegen der sichtbaren Narbenbildung propagieren manche Autoren die Korrektur über den medialen Zugang ggf.…”
Section: Secondary Reconstruction Of the Elbow Joint In Childhood Absunclassified